The translational landscape of fission yeast meiosis and sporulation - Duncan, Caia D. S. (2014)
Sexual development in the fission yeast Schizosaccharomyces pombe culminates in meiosis and sporulation. We used ribosome profiling to investigate the translational landscape of this process. We show that the translation efficiency of hundreds of genes is regulated in complex patterns, often correlating with changes in RNA levels. Ribosome-protected fragments show a three-nucleotide periodicity that identifies translated sequences and their reading frame. Using this property, we identified 46 novel translated genes and found that 24% of non-coding RNAs are actively translated. We also detected 19 nested antisense genes, in which both DNA strands encode translated mRNAs. Finally, we identified 1,735 translated upstream ORFs in leader sequences. In contrast with Saccharomyces cerevisiae, sexual development in S. pombe is not accompanied by large increases in upstream ORF use, suggesting that this is an organism-specific adaptation and not a general feature of developmental processes.